Antiquities Policies and Museology Activities in the Ottoman Empire - Gungor, Medine (My University, 2024)
ABSTRACT The roots of Turkish Museology are based on the Mecma-ı Asar-ı Atika (Collection of Ancient Artifacts), which forms the foundation of the Istanbul Archaeology Museums. In 1845, during a visit to Yalova, Sultan Abdülmecit decided to transfer Eastern Roman inscriptions to Istanbul after seeing them, leading to the collection of artifacts in Hagia Irene, which had been used as an arsenal until then. The museum was organized into two sections: Mecma-i Eslihai Atika and Mecma-i Asar-ı Atika. The former, dating back to earlier periods, laid the groundwork for the Harbiye Military Museum. The Mecma-i Asar-ı Atika collection was curated during the tenure of Grand Vizier Ali Pasha and established as the Ottoman Empire's first museum in 1869 under the name \"Müze-i Hûmayun\" by the Minister of Education Saffet Pasha. Edward Goold, a teacher from Galatasaray High School, was appointed as the museum's first director in the same year. A decree was issued instructing provinces to send historical artifacts to the museum without damaging them, and the Asarı Atika Regulations came into effect within the same year.As the number of collected artifacts increased, a search for a new building commenced, leading to the decision to move the museum to the Tiled Kiosk. The museum, relocated to the Tiled Kiosk, became operational in 1880. Following the death of Museum Director Anton Dethier, the search for a new director began. Osman Hamdi Bey, who holds a significant place in Turkish Museology history, was appointed to this position on September 11, 1881. During that period, there was a lack of regulations to prevent individuals from abroad engaging in archaeological excavations and potentially looting archaeological sites. Therefore, the Asar-ı Atika regulations were issued to control and register excavations.
Keywords: Museology; Asar-ı Atika; relic policies